The Effect of Foot Soak Using Red Ginger Water and Physical Activity on Blood Pressure Reduction - Ali, Irpan Ali Rahman; Kusumawaty, Jajuk; Nurapandi, Adi; Fadilah, E Khoridatul (International Journal of Nursing and Health Services (IJNHS), 2023)
Introduction: Hypertension is a deadly disease known as a silent killer and fourth rank in West Java province such 29.4% of cases. Management of hypertension can be done with pharmacological or non-pharmacological therapy. Red ginger is one of the non-pharmacological therapies. Objective:  This study aims to determine the relationship between foot soaking using red ginger water and physical activity on decreasing blood pressure level in Sakawayana Village. Method: This study was a one-group, pretest-posttest quasi-experimental design. The number of samples in this study was 40 people that was selected based on inclusion criteria. Result: This study indicates that the average blood pressure after receiving foot soak therapy using red ginger water and physical activity was 147.4 mmHg systolic pressure and 91.5 mmHg for diastole with a p-value <0.05. Conclusion:  There is a relationship between foot soaking using red ginger water and physical activity in lowering blood pressure in Sakawayana Village. Recommendations: Further study need to apply this intervention with different population to ensure the effectiveness of red ginger therapy for health outcomes